STUDI KASUS LAJU KOROSI BALING-BALING PERAHU NELAYAN DI DESA TANJUNG TIGA SUBANG JAWA BARAT - Arbintarso, Ellyawan; Yusup, Mad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
Rotated of small motorboat propellers produced relative motion among propeller and fluid media (water) i.e. mechanical effect as thrust, cavitation and friction. The me-chanical effect with chemical and electrochemical reaction resulted corrosion on mo-torboat propellers. Tanjung Tiga was choosen with geographic reason, that can be a mo-del for the other place along north beach of Jawa Barat, which fisherman went to sea via muddy estuary. Erosion, pitting, cavitation and galvanic corrosions happened on small motorboat propeller. Increasing 10 % of rotation of propeller made corrosion rate higher more than 80%, because the estuary muddy and made shallow, the propeller have hard impacted when on river than on the sea.